Tpack Profile of Physical Education Teacher in Bandung City - Masruri Ramdani Pathurohman; Agus Mahendra; Dian Budiana; Hasanul Fitrah Alba (Universitas PGRI Palembang, 2023)
Physical teacher education is required to develop using technology, namely to improve planning and application in learning, but there are obstacles for a teacher to innovate by combining technology in Physical education. Integration of technology and learning Physical education demands the incorporation of surrounding pedagogy into knowledge, pedagogy, content and technology (TPACK), is a framework for integrating technology into learning that can be used in all subjects in general. Especially in physical education, of course, it has a unique relationship with technology when compared to other subjects, because physical education is fundamentally different from teaching other subjects, many the way in which some studies have touched on the framework of TPACK and Physical Education. The TPACK framework describes the type of knowledge required by teachers for successful integration of technology in teaching expands the work and argues that teachers should develop a complex, located, and integrated body of knowledge, known as technological pedagogical content knowledge (TPCK), or more recently as technological, pedagogical, and content knowledge (TPACK). Technological Pedagogical Content Knowledge (TPACK) is a framework that identifies knowledge, teachers need to teach effectively with a technological framework. As follows: TPACK was first introduced The instrument used is a questionnaire that has 7 components of the TPACK with 20 questions using a likert scale with respondents, namely physical Education teachers in the city of Bandung with the category of State Elementary Schools. Results of the study